Evaluación de la mezcla de etileno vinil acetato (eva) con caucho natural o sintético, para la incorporación en la formulación de suelas y cintas de calzado de la compañía Croydon Colombia S.A. (2018)
The objective of this project is to evaluate the mixture of Ethylene Vinyl Acetate (EVA) with natural or synthetic rubber for the formulation of shoe outsoles and footwear tapes in Croydon Colombia S.A., varying the percentage of the copolymer and evaluating its properties, to select the one with the most satisfactory results for use in the mentioned footwear parts. To carry out the above, the standard formulation is diagnosed from the measurement of abrasion, elongation, ripping, tension, bending, hardness and density, noting that these values ​​are within the limits of acceptance of the company. In the experimentation stage, 12 formulations are developed with natural rubber (NR), polybutadiene (CISD), styrene butadiene rubber 1502 (SBR 1502), and styrene butadiene rubber 1205 (SBR 1205), modifying the amount of EVA in three levels: 5, 10 and 15 PHR, the dicumyl peroxide being the vulcanizing agent and the same properties of the diagnostic step are measured. The formulation based on EVA-rubber that reported the best results is the 5 PHR of EVA and 95 PHR of CISD, which presented an average value of abrasion of 205.45 mm3, elongation of 853.67%, ripping effort of 7913.47 N/m, bending strength of 26 mm breaking at 92500 cycles, tension of 4.11 MPa, hardness of 50.93 Shore A and density of 1.05 g/mL.